Center state financial relations in India - Birla Institute of Scientific Research, Economic Research Division (New Delhi, 1979)
The present Study addresses itself to the task of an objective analysis of current dissatisfaction with Centre-State financial relations in India. A description of the basic nature of this dissatisfaction is followed by theoretical underpinnings of federal financial relations and a bird's overview of the relevant Constitutional provisions regard ing federal resource transfers in some other countries. Underlying causes of the malfunctioning of Centre-State financial relations in India, which have created a vicious circle of their own, have been analyzed with reference to our Constitutional provisions and an assessment of the attitudes and roles of the Finance Commis sion, the Centre and the States. There is a detailed discussion of the working of the Finance Commission which, according to the findings of this Study, is the point from where corrective measures should start. Analysis of the system in operation is highlighted with that of specific problems like mounting indebtedness of the Stater States to the Centre. also a discussion and There is also specification of corrective measures indicated by the findings of the factual analysis system and its working.
Keywords: Finance, Public India